1977
DOI: 10.1002/ijc.2910190504
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis associated with human neoplasia: Production of plasminogen activator by human tumours

Abstract: The plasminogen-dependent fibrinolytic activity of several human tumours has been studied. The following neoplastic tissues, which were obtained from cancer patients by either surgery or biopsies, were examined: cervical, mammary. prostatic, ovarian, lung carcinomas, melanoma, basalioma. Fibrinolysis was measured in lysates either of tumour tissue specimens or of respective cell cultures. This measurement was based on release of radioactivity from '2s1-fibrin-coated Petri dishes. All examined tumours showed el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Conversely, hyaline membrane disease in premature infants has been associated with low fibrinolytic activity (36). Nagy et al analyzed lysates of several human tissues and found that only lung tissue contained large amounts of plasminogen activator (37). Alpha-2-macroglobulin inhibits a very wide spectrum of neutral proteases, including bacterial proteases, plant proteases, elastase, collagenase, and plasmin (1).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, hyaline membrane disease in premature infants has been associated with low fibrinolytic activity (36). Nagy et al analyzed lysates of several human tissues and found that only lung tissue contained large amounts of plasminogen activator (37). Alpha-2-macroglobulin inhibits a very wide spectrum of neutral proteases, including bacterial proteases, plant proteases, elastase, collagenase, and plasmin (1).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have indicated increases in the level of plasminogen-dependent fibrinolytic activity after transformation of early-passage cultures by both viruses and chemical carcinogens Ossowski et al, 1973;Jones et al, 1976;Pearlstein et al, 1976), in cell lines derived from experimentally produced tumours in animals (Laug, Jones and Benedict, 1975;Pearlstein et al, 1976) and in the cells of, or cell lines derived from, human neoplasms (Laug et al, 1975;Nagy, Ban and Brdar, 1977).…”
mentioning
confidence: 99%
“…There is a substantial (although still imperfect) correlation between increased fibrinolytic activity and malignancy (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Resultsmentioning
confidence: 99%